Long-term creep behavior of self-reinforced PET composites - C. M. Wu; P. C. Lin; R. Murakami (eXPRESS Polymer Letters, 2017)
Creep deformation of polymers results from their inherent viscoelastic nature that changes polymer’s shape with time. Creep response represents an important property of thermoplastic composites that affects their dimensional stability, especially in applications requiring the material ability to support relatively high loads for long periods. This work examines the creep behavior of self-reinforced recycled poly(ethylene terephthalate) (srrPET) composites, which were produced by film stacking from fabrics composed of double covered uncommingled yarns with recycled PET homopolymer filaments (serving as the reinforcements) and copolymerized PET (mPET) filaments (serving as the matrix). The short-term creep behavior of both srrPET and mPET was studied in the single cantilever mode below and above the glass transition temperature, and the obtained data were analyzed using the Findley’s viscoelastic and Burgers four-element models. The long-term creep behavior of srrPET specimens with and without open circular holes was described using an Arrhenius-type time–temperature superposition principle.